Forced or Induced Saving: An Exploration into Its Synonyms and Homonyms - Machlup, Fritz (The Review of Economics and Statistics, 1943)
C ONCEPTS and terms, in every-day use as 'A well as in scientific use, have often peculiar histories. A concept is usually an adaptation of an old one which suggests itself to observers of a phenomenon as they attempt its interpretation. If the new concept is still unnamed, they name it after some other idea that appears to them as an appropriate simile or metaphor. The chosen name, however, may suggest to others some slightly different associations and, therefore, altered concepts. Moreover, changes of the frame of reference, or of the angle from which the phenomenon is looked upon, may require remodeling of a concept. But the remodeled concept may still pass under the old name. Other observers come along, dislike the name, and suggest different ones. Synonyms develop. Most or all of the terms which are then used for the growing family of concepts have had previous uses, and many of the terms are again put to new uses. Homonyms and equivocations grow in number. Makers of dictionaries must list more and more meanings under each name and must give more and more synonyms for each meaning. To complain about the continuous change of concepts and terms, about the conversion of ideas and names, is to misunderstand the nature of growth of a body of knowledge at least in the social sciences. Attempts to halt the development (for example, through the establishment of committees on nomenclature and terminology) are in vain and often deplorable. To be sure, wilful innovators sometimes suggest change merely for the sake of change. If concepts and terms shift like women's fashions, the change may confuse discussion and become a nuisance.' But otherwise. we must accept it as a fact that new problems and new treatments of old problems may require changes in concepts and in terms. When the family of related concepts related by meaning or by name or both is large, an occasional examination of the family record and a probing of the relationships is helpful. Old confusions may be clarified, and new confusions avoided, through such an examination. And better understanding of the concepts usually results in better understanding of the phenomena whose explanation they are to serve. This article will survey and briefly analyze the various concepts connoted by the term forced saving, and the various terms assigned to its basic idea.